Teologia ecológica: perspectivas para a espiritualidade e a vivência pastoral - Rodrigues, Danilo (2022)
The present research presents reflectionson ecological theology considering its development in theological thought. The first chapter aims to expose what ecological theology is; seeking to present definitions for the words ecology and ecotheology. Therefore, our exhibition will present the destruction of nature in its various realities. Fires and deforestation are every day reducing biodiversity to a small space, and life in the countryside becomes unfeasible for the poor who love and cultivate the soil with respect. Public authorities can no longer be silent in the face of the threatening situations that planet Earth is experiencing. Ecotheology presents us with pastoral actions in which we find the spirituality of care. It is urgent to discover the paths towards an integral ecotheology and at the same time demand concrete attitudes from our rulers, but it is necessary to change our ways with nature; we are not their masters but collaborators.With the second chapter, we will ponder the reflections on the care of the Earth and the commitment of society so that nature is respected and continues to offer us, free of charge, what we need to survive. We are depleting the resources that were renewable and in this way life on the entire planet is compromised. At this point, Jürgen Moltmann reflections will guide us to understand that the Earth is part of Creation and is not our slave. Living together and caring is an urgent necessity if we want to have a future for life on Earth. Leonardo Boff and his comments on the Earth Charter offer us many arguments for a respectful coexistence with all the species of life that inhabit this wonderful planet with us. Still in the second chapter, we will comment on the writing of Laudato Si –its reflections for an integral ecology.In the third chapter we will present the ecotheological proposals proposed by Leonardo Boff and we will approach two recent documents of the Church: Instrumentum laborisand the Apostolic Exhortation Querida Amazônia. In these documents we reflect the interrelationship and communion with magnificent ideas; there is no way to live on Earth and we do not realize the deep relationship with nature and the environment. Ignoring interrelation and communion is heading towards the destruction of all life on our planet. Sad events in history reveal the arrogance of colonizers who started a cycle of death that continues to this day. The Amazon region, a land of mission in danger, asdescribed in the document Instrumentum laboris, from which we point out the initial ideas of the bishops and people of Panama during the synod of bishops.